2022
DOI: 10.1021/acsami.2c14271
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Oxide-Modified Concentric Microgrooved Titanium Surfaces for the Dual Effects of Osteogenesis and Antiosteoclastogenesis

Abstract: Surface modification is an effective method to resolve the biocompatibility, mechanical, and functional issues of various titanium implant materials. Therefore, many researchers have modified the implant surface to promote the osseointegration of the implant and improve the implant survival rate. In this study, we used photolithography to construct concentric microgrooves with widths of 10 μm and depths of 10 μm, to produce an osteon-mimetic concentric microgrooved titanium surface that was further modified wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…OCN emerges towards the end of osteoblast differentiation; it binds to Ca 2+ ions to regulate calcium homeostasis and promote bone mineralization while also contributing to the maturation and mineralization processes of osteoblasts [61]. Numerous studies have demonstrated that GO composites possess regenerative properties for nerves [62], blood vessels [63], and particularly for bone tissues [17]. This may be attributed to abundant functional groups on GO surfaces providing a unique platform for promoting osteogenesis through various pathways such as PI3K/Akt/GSK-3β/β-catenin signaling pathway, actin cytoskeleton dynamics or ERK signaling pathway [64,65].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…OCN emerges towards the end of osteoblast differentiation; it binds to Ca 2+ ions to regulate calcium homeostasis and promote bone mineralization while also contributing to the maturation and mineralization processes of osteoblasts [61]. Numerous studies have demonstrated that GO composites possess regenerative properties for nerves [62], blood vessels [63], and particularly for bone tissues [17]. This may be attributed to abundant functional groups on GO surfaces providing a unique platform for promoting osteogenesis through various pathways such as PI3K/Akt/GSK-3β/β-catenin signaling pathway, actin cytoskeleton dynamics or ERK signaling pathway [64,65].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that GO effectively induces osteoblastic differentiation in bone marrow mesenchymal stem cells [16]. Wang et al [17] demonstrated that surface modification of titanium implants with GO not only promotes osteogenic differentiation of BMSCs but also effectively inhibits osteoclasts. Shao et al [18] found that the addition of GO into PLGA/tussah silk scaffolds significantly enhances the osteogenic differentiation capacity of mesenchymal stem cells (MSCs).…”
Section: Introductionmentioning
confidence: 99%